LOS PRONÓSTICOS DE CONSUMO ANTE EL RETO DEL TRATADO DE LIBRE COMERCIO - Aguero del Carpio, Lizardo (2006)
The Free Trade Agreement with the United States, represents an enormous opportunity for all those businesspeople who want to expand their horizons and make their products to be accepted due to their competitiveness. For this reason they have to make business business activities employing all those managerial tools at their service. This is vital because they will permit to handle adequately the existing resources in the organization and above all to handle the internal structure of costs, using mathematical calculations and statistics to mitigate the inherent risks in every business activity. The current article, pretends to prove that the use of the managerial tools statistics and mathematics and in business management which allow them to make the appropriate decisions to achieve the fundamental objective of being positioned in a widely competitive market.